2021
DOI: 10.3390/jpm11090925
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Estrogen-Responsive Genes in Women with Psoriasis

Abstract: In women, the flow of psoriasis is influenced by each phase of a woman’s life cycle. According to previous findings, significant changes in the levels of sex hormones affect the severity of the disease. Aim: The aim of this study was to identify the estrogen-responsive genes that could be responsible for the exacerbation of psoriasis in menopausal women. Methods: Skin samples of lesional skin donated by psoriasis patients (n = 5) were compared with skin samples of healthy volunteers (n = 5) using liquid chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…A detailed study of disease-associated proteins revealed 123 DEPs in lesional and normal-looking skin of female patients. Contrarily, their expression did not significantly change in similar samples of male patients [48]. The following ontology analysis discovered 14 overrepresented biological processes.…”
Section: The Analysis Of Differentially Expressed Proteins In the Skinmentioning
confidence: 91%
See 3 more Smart Citations
“…A detailed study of disease-associated proteins revealed 123 DEPs in lesional and normal-looking skin of female patients. Contrarily, their expression did not significantly change in similar samples of male patients [48]. The following ontology analysis discovered 14 overrepresented biological processes.…”
Section: The Analysis Of Differentially Expressed Proteins In the Skinmentioning
confidence: 91%
“…The signs  and  indicate that the protein expression is increased and decreased, respectively. The sign  indicates that chemical reaction between HCO3 − and can be reversed [48].…”
Section: The Analysis Of Differentially Expressed Proteins In the Skinmentioning
confidence: 99%
See 2 more Smart Citations
“…Sobolev et al found a differential expression of six estrogen-controlled genes (HMOX1, KRT19, LDHA, HSPD1, MAPK1, and CA2) in the skin of female patients with psoriasis compared to male patients with psoriasis and concluded that these proteins may be involved in the defense of skin cells against inflammation damage. Considering that estrogens exert anti-inflammatory effects, low estrogen levels can influence the course of the disease in women with psoriasis [ 6 ]. Using a mouse model of induced psoriatic dermatitis, Surcel et al obtained promising results after the administration of IgY, which led to the improvement in skin lesions and the normalization of immune parameters.…”
mentioning
confidence: 99%